(untitled) (Fiep Bulletin - online, 2015)
Muay Thai is a martial art and a method of self-defense with rules different from other martial arts. Muay-Thai in any part of the body remains inactive, physical strength and intellect are qualities necessary that every fighter must possess. (KRAITUS, 1988, quoted by DELP, 2005). The anti-stress massage is a manual technique that touches methodical aims therapeutic action, aid in the elimination of catabolic the body’s relaxation benefits, acting mainly in the circulation and into the venous and lymphatic return. (NESSI, 2010). The massage acts on the pains of the athlete, but is indicated only when there is no injury, but mostly, the contrary to prevent injuries. (McGillicuddy, 2011). CASSAR (2001) cites that the athlete often muscle fatigue occurs when a muscle is overused disturbing the physiological process of the same. This work aims to verify the benefits of anti-stress massage adapted for athletes 20-45 years male and female before and after fights (competition) Muay-Thai. Through two sessions of Massage Sequence for Lower Limb Anterior and Posterior Region and Coasts in each volunteer. Each massage session was performed 15 minutes of massage pre-training and 30 minutes post-treinamento.Todos athletes showed high stress and anxiety before the massage, as well as muscle aches, after the stress is less than 20% while the pain also decreased since the feeling of well-being was low before the massage, after showing a sense of well-being 100%. The feeling of relaxation before too was low after the result was great. We conclude that massage can greatly benefit the athletes, but needs further study in the medium and long term.